THE DYNAMICS OF THE FREQUENCY OF LOWER LIMB AMPUATATIONSIN THE CITY OF NOVOKUZNETSK: A RETROSPECTIVE STUDY - Васильченко, Елена Михайловна (Medicine in Kuzbass, 2018)
The dynamics of the frequency of lower limb amputation in the population of Novokuznetsk during 1996-2015 was analyzed based on the local registry of patients with amputations. The author found that the frequency of lower limb amputations due to peripheral arterial obliterative disease increased by 1,9 in the end of the study period. This change is associated with a dramatic increase in the frequency of amputations both among men and women, mainly among those older than 70 years of age. The increase in the frequency of amputations was larger among women.
Keywords: lower limb amputation; arterial obliterative disease; frequency of amputations; case follow-up